2021
DOI: 10.3832/ifor3648-014
|View full text |Cite
|
Sign up to set email alerts
|

Are we ready for a National Forest Information System? State of the art of forest maps and airborne laser scanning data availability in Italy

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry Are we ready for a National Forest Information System? State of the art of forest maps and airborne laser scanning data availability in Italy Giovanni D'Amico (1) , Elia Vangi (1-2) , Saverio Francini (1-2-3) , Francesca Giannetti (1-4-5) , Antonino Nicolaci (6) , Davide Travaglini (1) , Lorenzo Massai (4-5) , Yamuna Giambastiani (4-5-7) , Carlo Terranova (8) , Gherardo Chirici (1-5) Forest planning, forest management, and forest policy require updated, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…The study area coincides with the Italian area hits by the VAIA windstorm as reported by Chirici et al (2018) [47] in the following Regions of Italy: Trentino Alto Adige, Veneto, Friuli Venezia Giulia, Lombardia, Piemonte, and Valle d'Aosta (Figure 1), for a total of 67,000 km 2 covered by forest for 144,651.1 ha following the FAO forest definition [48,49]. The VAIA storm hit the area in the night between 28 and 29 October 2018 with winds up to 200 km/h [45].…”
Section: Study Area and Vaia Windstormsupporting
confidence: 69%
See 2 more Smart Citations
“…The study area coincides with the Italian area hits by the VAIA windstorm as reported by Chirici et al (2018) [47] in the following Regions of Italy: Trentino Alto Adige, Veneto, Friuli Venezia Giulia, Lombardia, Piemonte, and Valle d'Aosta (Figure 1), for a total of 67,000 km 2 covered by forest for 144,651.1 ha following the FAO forest definition [48,49]. The VAIA storm hit the area in the night between 28 and 29 October 2018 with winds up to 200 km/h [45].…”
Section: Study Area and Vaia Windstormsupporting
confidence: 69%
“…), however some damages were reported also in broadleaves forests such as in beech stands (Fagus sylvatica L.) [48]. Preliminary field recognition and manual photointerpretation of satellite data showed that a total of 42.525 ha of forests were damaged by the storm [47,49]. The minimum mapping units used to delineate damaged area was 2000 m 2 and the areas were considered damaged if at least 50% trees fallen.…”
Section: Study Area and Vaia Windstormmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in the approximately 11 million hectares of Italian forest land, as defined by the last national forest mask (Figure 1) [40,41]. A remarkable variability of vegetation characterizes the Italian peninsula due to a wide diversity of geographical and morphological conditions.…”
Section: Study Areamentioning
confidence: 99%
“…To create a historical GIS, however, in addition to a thorough bibliographic work, it is necessary to use techniques that allow for minimizing cartographic errors inherent in the historical cartography used [62]. New open-source applications and the interoperability of QGIS with other tools provide methodologies of semiautomatic and manual georeferencing and digitization that speed the work without losing accuracy.…”
Section: Historical Gis To Understand How Much and Where Forests Have...mentioning
confidence: 99%